Implementasi Sertifikasi Halal Self Declaire Pada Usaha Mikro Dan Kecil Di Surabaya - Erwan Aristyanto; Agus Sarwo Edi (Universitas Sains dan Teknologi Komputer, 2023)
. The aim of the research is to find out, analyze and evaluate the implementation of halal certification for micro and small businesses through BPJPH and to find out, analyze and evaluate how halal certification through BPJPH works for micro and small businesses in the city of Surabaya from an Islamic economic perspective. This research was carried out in accordance with the strategic research plan of Wijaya Putra University for 2020 - 2024 in the leading areas of managing innovation & creative industry with research topics on standardization and competitiveness of MSMEs and creative industries. This research uses descriptive qualitative research methods. This research data was collected through observation, interview and documentation techniques which were validated through method triangulation and source triangulation techniques and then analyzed through the stages of data collection, data reduction, data presentation and drawing conclusions and verification. The findings of this research are that the BPJPH self-declaration halal certification process for micro and small businesses in 2023 in the city of Surabaya which is dominated by food products rather than beverage products is carried out in several stages. First, registration is carried out online on the halal application and accompanied by a halal process companion from a BPJPH representative institution bringing the specified documents. Second, the halal process assistant from the BPJPH representative agency will carry out an inspection to check the suitability of the completeness of the files in the field. Third, holding a fatwa commission hearing to assess whether the product can be accepted or rejected. Fourth, products accepted at the fatwa commission hearing will be approved for certification. Halal certification in a sharia economic perspective applies three ethical principles, namely, aqidah, shiddiq, and amanah which are related to the urgency of halal certification not only for consumers but also business actors, including, among other things, the importance of eating halal food, providing guarantees and a sense of security as well as consumer protection